Strategi Dinas Kebudayaan dan Pariwisata Kota Tanjungpinang dalam Pemulihan Sektor Pariwisata pada Situasi Pandemi Covid -19 - Indriyati, Susana; Nadia, Putri; Siti Utari, Diah; Dwiniati, Dwiniati; Ramdhani, Yudi (Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
No foreign tourists visited Tanjung Pinang in July 2020 as international passenger ships have been suspended since April 2020 due to the Covid-19 pandemic. In July 2020, there were 1,765 tourists visiting the Riau Islands, 1,754 (99.38%) from the entrance of Batam City and 11 (0.62%) from the entrance of Bintan Province. On the contrary, in July 2020, no foreign tourists visited Tanjung Pinang City. Since no tourists visited Tanjung Pinang City in July 2020, the number of tourists visiting Tanjung Pinang City, decreased by around 81.71 percent compared to the same period last year. The purpose of this study was to determine the Strategy of the Tanjungpinang City Culture and Tourism Office in the recovery of the tourism sector in the covid-19 pandemic situation. The result of this study is that the Tanjungpinang City Culture and Tourism Office on the recovery of the tourism sector in the covid-19 pandemic situation has not been optimal because it sees weaknesses both internally & externally, this is found in the following, namely the tourism office is still carrying out tactics before covid, even after covid this has not been formulated specific strategies. Tourism development is needed, development of tourism destinations & development of human resources (HR). The Tanjungpinang City Tourism Office has collaborated using particulate parties to increase the tourism potential of the region tourist visits to the Tanjungpinang City area.